Metal Saturated Cumulates from Siberia — Lunar Basalt Analogues? - Ballhaus, Chris; Leitzke, Felipe P; Fonseca, Raúl O C; Nagel, Thorsten; Kuzmin, Dmitri; El Goresy, Ahmed (Journal of petrology, 2022)
Abstract It is not well known which chemical differentiation pathways basaltic melts will take when they are iron metal saturated. Thermodynamically, the pathway seems predictable. So long as Fe metal is a stable liquidus phase and relative oxygen fugacity (fO2) is not subject to major fluctuations, the activity of FeO (aFeOmelt) is buffered by the iron–wüstite (IW) equilibrium 2Femetal + O2 → 2FeOmelt. Metallic Fe also stabilizes olivine through the equilibrium 2Femetal + O2 + SiO2 melt → Fe2SiO4 olivine. That equilibrium tends to suppress the enrichment in bulk SiO2 when Fe saturated basaltic melts differentiate. We document the differentiation history of tholeiitic cumulates from the Siberian craton that carry up to 30 modal % metallic Fe. Our study is complemented by differentiation experiments at two redox states, one set in Fe metal capsules at 1.6 log units below IW (IW-1.6) and a second set in graphite capsules at IW + 1.5. Iron saturated differentiation pathways do not show enrichments in FeO nor in bulk SiO2 because olivine remains stable along the entire liquid line of descent. By contrast, melts equilibrated at IW + 1.5, that is, outside metallic Fe saturation, crystallize pigeonite as first silicate and follow a normal (terrestrial) differentiation pathway involving marked SiO2 enrichment. The Fe-saturated path duplicates in detail the liquid line of descent we derive for the cumulates. Iron-saturated experiments have limited applicability to the Earth because there are so few terrestrial basalts saturated with metallic Fe; however, they might apply to the Moon. Many lunar basalts appear to have been saturated with an Fe-Ni phase during their emplacement on the lunar surface, and potentially during generation within the lunar mantle.